Design and fabrication of exhibition rack - Mohamad Hanapi, Mohamad (2007)
Manufacturing is a process of converting raw material into product. It can be described the transformation of materials into items of greater value by means of one or more processing andJor assembly operations. The study of manufacturing was very important in order to carry out this project to ensure that student understand on what are needs to do. This project is about designing and fabricating the Exhibition Rack that can be used to display many item.. This project involves the process of designing the exhibition rack by considering the shape, functionality, durability and manufacturing cots for people to use it. The material of this design is easy to gain it, because it only using rectangular steel, sheet metal, L- shapes steel and Perspex. So that the method joining that can be compatible in assembled this exhibition rack, rivet pop process and welding processes. This project also required analysis to make sure the strength of the product and ensure the safety for the user indeed of publishing. After all the process had been done, this clothesline may help us to understand the fabrication and designing process that involved in this project.